엔드밀의 TiN 코팅조건과 절삭력 증가율과의 관계 - 최석우(Choi Suk Woo); 이위로(Lee Wi Ro); 최광진(Choi Kwang Jin); 백영남(Paik Young Nam) (Biuletyn Uniejowski, 2001)
TiN coating of high speed end mill is recently generalized. The study of coating layer using ion plating is mainly about the coating method and the why of the longer life of coated tools. In CNC machning process, metal cutting isn't carry out until the tools including the end-mill and so on are fractured. Namely, it is difficult precision processing when the cutting force of the cutting tool is near the limit the fracture cutting force. So, the estimate of the life by wear and fracture is important. Therefore, this study is about the method to estimate the capacity of the coating layer in relation to the tendency of cutting force and the influence of the cutting capacity of coated end-mill by the condition N2, Ar, temperature. The cutting length is in inverse proportion to the cutting force ratio. So, the life of the TiN coated end mill can be predicated by the ratio of the increase of the cutting force.